Mitochondria Transfer in Brain Injury and Disease - Lauren H. Fairley; Amandine Grimm; Anne Eckert (Cells, 2022)
Intercellular mitochondria transfer is a novel form of cell signalling in which whole mitochondria are transferred between cells in order to enhance cellular functions or aid in the degradation of dysfunctional mitochondria. Recent studies have observed intercellular mitochondria transfer between glia and neurons in the brain, and mitochondrial transfer has emerged as a key neuroprotective mechanism in a range of neurological conditions. In particular, artificial mitochondria transfer has sparked widespread interest as a potential therapeutic strategy for brain disorders. In this review, we discuss the mechanisms and effects of intercellular mitochondria transfer in the brain. The role of mitochondrial transfer in neurological conditions, including neurodegenerative disease, brain injury, and neurodevelopmental disorders, is discussed as well as therapeutic strategies targeting mitochondria transfer in the brain.